-3n-4=-3n+1

Simple and best practice solution for -3n-4=-3n+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3n-4=-3n+1 equation:


Simplifying
-3n + -4 = -3n + 1

Reorder the terms:
-4 + -3n = -3n + 1

Reorder the terms:
-4 + -3n = 1 + -3n

Add '3n' to each side of the equation.
-4 + -3n + 3n = 1 + -3n + 3n

Combine like terms: -3n + 3n = 0
-4 + 0 = 1 + -3n + 3n
-4 = 1 + -3n + 3n

Combine like terms: -3n + 3n = 0
-4 = 1 + 0
-4 = 1

Solving
-4 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

You can always share this solution

See similar equations:

| 4s-1=1 | | -7u-13-3u=19-10u | | 6x-60=90 | | 8x+70=3y | | 5a-2a-5+1=-12 | | 9+17-2y=5y-16 | | 13=3(x-1)(x-8) | | $213.85(1-0.095x5/12) | | 15=37 | | 15=33 | | 5x-6x=-x | | 9w-17=-3-14+9w | | -20h+17=17-20h | | -2-2m=-18m-11+16m | | X-11/3 | | -15p+6p-8=11-9p | | 12-4x=2x-8 | | -14k-1=-14k+1 | | X+-9=14 | | r-(-17)=12 | | 6x+1y=-31 | | 6n+10=8n-8 | | 52.5-24x+1.2x^2=0 | | (2x+10)+(2x+12)=90 | | 18+5x=3(10-x) | | x^3-3x^3=0 | | -8c+10=-8c-4 | | 1/3n-2/9 | | 2v-8=10-v | | 5x+2=-3+6x | | 4x+49+2x+11=90 | | 10-m=41 | | 20x-35=65 | | 5x=50-5x | | 3.4+(3.8+j)= | | 200x+315=50x-450 | | 4.4(-5+1.1h)= | | 13=3(x-1)-(x-8) | | 4x^2-17x+11=-4x+2 | | -8+6f=3f+10 | | 4x-3+x=52 | | -1.2(-1.3t)= | | 200=40x-90 | | 10-4r=-4r+10 | | 6(-5u+1)= | | 8x+50+(-5x)+34=90 | | ln(x)=(x^2)+1 | | -3+(v+4)= | | -1+3d=6+2d | | (3z)(-8)= | | 7/9k=5/15 | | -4(-6+7r)= | | w+-8=0 | | 2(12-k)-(k+2)=8(2-3k)-3(5-6k) | | 5x+650=5 | | 6+x=97 | | -5t+7t=h(t) | | 1+10g=-8+10g | | 6(-7+2d)= | | 15x-25=65 | | -1+(m+-4)= | | -9s=7-9s | | -5-6t=-6t-3 | | 3x+36=2x-45 | | -16t^2+940=h |

Equations solver categories